Calamities, the Subsequent School Closure, and Their Impact on Adolescents’ Mental Health - Srilatha K Paslawar; Sudha Kallakuri; Sandhya Kanaka Yatirajula; Mercian Daniel; Pallab K Maulik (Indian Journal of Public Health)
This article aims to understand the implications of calamities and the resulting school closures on the mental health of adolescents. The impact of calamities, such as natural disasters or pandemics, on school closures and adolescents’ mental health is complex. It is crucial to provide the necessary support, resources, and interventions to help adolescents navigate these challenging times and minimize the long-term impact on their mental well-being.